Historical trends associated with annual temperature and precipitation in Aegean Turkey, where are we heading? - Mersin, Denizhan; Tayfur, Gökmen; Vaheddoost, Babak; Safari, Mir Jafar Sadegh (My University, 2022)
The trend analysis of annual temperature (daily average) and total precipitation has been conducted for 14 stations located in the Aegean Region, Turkey. The Sen, Spearman's rho, and Mann-Kendall test methods are used in the detection of the historical trends in the region. The Pettitt test is also implemented to find the significance of the trend, while the Theil-Sen approach is applied to detect the change point(s) in the time series. Findings of the following study indicate that both precipitation and temperature time series in the selected stations depict statistically significant trends with increasing nature. The rate of increase in precipitation and temperature by the Theil-Sen test is found to be 4.2-7.9 mm/year and 0.20-0.35 °C/decade, respectively. It is also found that the turn points of the temperature trends determined by the Pettitt test occurred in 1998 for all the stations. According to the results, the magnitude of the extreme events would change in the future, which may help in conceptualizing the framework and the resilience of the infrastructures against climate change.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hydraulics; Hydrology; Environment; Hydrometeorology; Civil engineering